Principles of civil government - Sen, Sachin (Bombay, 1932)
"Economics, which is neither more nor less than the academic name for the science of work and wealth, is spoken of in the 'Science of Life' as a branch of ecology; it is the ecology of the human species . . . . Eco nomics is the science of the balance of human life and how it prospers or decays.... Until recently economic science and discussion have ignored biology and out raged psychology; they have dealt with a sort of standard and inalterable man; it is only now that it becomes possible to bring economic realities into line with these more fundamental sciences and treat them as evolved and evolving facts."
Keywords: Economics